Proceedings of the Russian Conference on Digital Economy and Knowledge Management (RuDEcK 2020) 2020
DOI: 10.2991/aebmr.k.200730.076
|View full text |Cite
|
Sign up to set email alerts
|

Modernization of Quality Management System in the Conditions of Digital Transformation of Enterprise

Abstract: The subject of the study ischanging the conditions of functioning of the quality management system in the conditions of digital transformation of the enterprise management system. The purpose of the study is to develop methodological provisions for the modernization of the quality management system. The directions of changes are systematized in the article and the basic conditions for the implementation of quality management processes are formed taking into account the drivers of innovative development of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…In our literature reviewand in line with the findings of the bibliometrics analysiswe found that the most common topics on Quality 4.0 are technology and its implications for IJQRM 39,6 quality (P erez-Ar ostegui et al, 2015;Yadav et al, 2020), implications for business management and strategy models and systems (Menshikova et al, 2019;Logunova et al, 2020) and human or soft factors (Domingues et al, 2019;Kannan and Garad, 2020a) In the next few sections we will revisit what has been written in regard to each of these topics.…”
Section: Results Of the Bibliometrics Analysissupporting
confidence: 68%
“…In our literature reviewand in line with the findings of the bibliometrics analysiswe found that the most common topics on Quality 4.0 are technology and its implications for IJQRM 39,6 quality (P erez-Ar ostegui et al, 2015;Yadav et al, 2020), implications for business management and strategy models and systems (Menshikova et al, 2019;Logunova et al, 2020) and human or soft factors (Domingues et al, 2019;Kannan and Garad, 2020a) In the next few sections we will revisit what has been written in regard to each of these topics.…”
Section: Results Of the Bibliometrics Analysissupporting
confidence: 68%